Category five : superstorms and the warming oceans that feed them - Fox, Porter (Little, Brown and Company, 2024)
Here is the story of the largest storms on earth and how those storms are growing bigger and stronger. The tale of extreme weather doesn't begin with floods, fires, or even the air that carries this change to our lives. It begins with the ocean. Oceans create weather, climate, floods, droughts, and most of the geophysical fallout of global warming. Exactly how, award-winning writer Porter Fox contends, depends on invisible ocean currents, planetary cycles just now being defined, and processes in the deep ocean that may well have already saved us from the worst effects of the climate crisis. In an attempt to avert a coming age of superstorms, sea level rise, and catastrophic warming, scientists followed the lead of a college drop-out-turned-maverick sailor and storm-chaser; a Romanian refugee turned BBC radio host turned circumnavigating mapmaker; and an audacious new attempt to study storms above as well as deep below the ocean depths, using drones.